Modulating the Band Alignments of Two-Dimensional In2Se3/InSe Heterostructure via Ferroelectric Polarization and Interlayer Coupling - Du, Yabing; Wang, Xiaolong; Dai, Xianqi; Li, Wei (Frontiers in Physics, 2022)
Two dimensional (2D) ferroelectric materials with robust polarization down to atomic thicknesses provide novel building blocks for functional heterostructures. While the effects of ferroelectric polarization on the electronic properties of 2D ferroelectric heterostructures are rarely investigated. Here, based on the first-principles calculations, we study the effect of ferroelectric polarization and interlayer coupling on the electronic properties of the 2D In2Se3/InSe ferroelectric heterostructure. It is found that the ferroelectric polarization of In2Se3 can effectively tune the band alignments of the In2Se3/InSe heterostructure. When the direction of ferroelectric polarization is reversed (i.e. from up to down), the band alignments of In2Se3/InSe heterostructures transition from type-I to type-II. Meanwhile, we find that the transition between type-I and type-II band alignment can be induced by means of interlayer coupling (i.e. varying interlayer distances). The results demonstrate that ferroelectric polarization and interlayer coupling are effective methods to modulate the band alignments of In2Se3/InSe heterostructures.